Overexpression of sprouty 1 protein in human oral squamous cell carcinogenesis - Yen-Yun Wang; Wen-Chen Wang; Chiang-Wei Su; Ching-Wei Hsu; Shyng-Shiou Yuan; Yuk-Kwan Chen (Journal of Dental Sciences, 2021)
Abstract Background/purpose: Sprouty (SPRY) has four isoforms, SPRY1–4, and its deficiency produces haphazard ‘sprouting’ of tracheal tubules. This study investigated SPRY1 protein expression in human oral potentially malignant disorders (OPMDs) and oral squamous cell carcinomas (OSCCs). Materials and methods: 90 OSCCs, 10 OPMDs with malignant transformation (MT), 17 OPMDs without MT, and six normal oral mucosa (NOM) tissue samples were subjected to immunohistochemical staining. Three human oral cancer cell lines (OCCLs), an oral precancer cell line (DOK), and a primary culture of normal oral keratinocytes (HOK) were used for western blotting. Results: Significantly increased expression of SPRY1 protein from NOM and OPMD without MT to OSCC was observed. The protein expressions of SPRY1 in OCCLs were significantly enhanced as compared with DOK and HOK. Increased phosphor/total-ERK expression was observed in OCCLs as compared with HOK. A significantly increased SPRY1 protein level was noted in OPMDs with MT as compared with those without MT, in addition to a significant increase in DOK in comparison with HOK. Conclusion: Our results indicated that overexpression of SPRY1 protein is potentially associated with human oral squamous cell carcinogenesis.